Evaluation of microfiltration and ultrafiltration membranes for improving water quality: removal of turbidity, suspended solids, and bacteria from the Tigris River - Al-Tamimi, Noor Jasim; Al-Alawy, Ahmed Faiq; Al-Shaeli, Muayad (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
The Tigris River in Baghdad is increasingly polluted by industrial and agricultural activities and untreated sewage, posing serious risks to public health and the environment. This pollution degrades water quality through various physical, chemical, and biological contaminants. This research aims to use membrane filtration techniques to treat Tigris River water, improving water quality and ensuring a clean, safe water supply. The study assesses the efficiency of polypropylene (P.P) 1µm, ceramic 0.5µm microfiltration, and polyvinylidene fluoride (PVDF) 500KD ultrafiltration membranes in removing turbidity, total suspended solids (TSS), and E. coli, and their impact on permeate flux. Experiments were conducted at a temperature of 25°C and a flow rate of 20 L/h, with regular intervals and an initial turbidity of 65 NTU. The results indicated that after 1.25 hours of operations, the permeate flux decreased by 23.12% for polypropylene membranes, 32.63% for ceramic membranes, and 38.48% for PVDF membranes. The PVDF membrane demonstrated the best performance, removing 98.7% of turbidity, 88% of total suspended solids (TSS), and 100% of E. coli. This makes it the most efficient membrane among the tested options. Hermia’s model was used to study fouling in crossflow ultrafiltration (UF) and microfiltration (MF) membranes. Results showed that cake formation and standard pore-blocking models best predicted flux behavior for the ceramic membrane, while complete and intermediate pore-blocking models were more effective for the PVDF membrane. This study shows that membrane filtration improves Tigris River water quality by removing turbidity, suspended solids, and bacteria, ensuring a safe water supply.